Recent advances in solid–liquid–gas three‐phase interfaces in electrocatalysis for energy conversion and storage - Jiang, Haosong; Luo, Ruihao; Li, Yimin; Chen, Wei (EcoMat (Beijing, China), 2022)
The acceleration of energy exhaustion and environmental pollution calls for the development of electrocatalytic conversion and storage technologies for the production and utilization of green energy. However, these technologies have encountered significant challenges in terms of poor selectivity, high overpotential, low efficiency, and sluggish kinetics of the electrocatalytic reactions, which involve solid–liquid–gas three‐phase interfaces (SLG‐TPIs). In this review, we focus on discussing recent progress on the development of SLG‐TPIs for electrocatalytic reactions, such as hydrogen evolution reaction (HER), oxygen evolution and reduction reactions (OER/ORR), and carbon dioxide reduction reaction (CO2RR), as well as their applications in water splitting, fuel cells, and metal‐air batteries. In addition, the working mechanism of TPIs is described and revealed by advanced characterization tools. The challenges and future opportunities of TPIs for electrocatalysis are also proposed in this review. This review focuses on discussing recent progress on the development of solid–liquid–gas three‐phase interfaces for electrocatalytic reactions of hydrogen evolution, oxygen evolution and reduction, and carbon dioxide reduction with applications in water splitting, fuel cells and metal‐air batteries.